Uncovering STEAM Research Patterns and Gaps: Systematic Literature Review in Education Journal - Neldarisasmita; Haryanto; Ervan Johan Wicaksana (Postgraduate, University of Mataram, 2025)
This study systematically analyzes trends, patterns, and research gaps in STEAM (Science, Technology, Engineering, Arts, and Mathematics) studies published in the JPPIPA Journal from 2021 to the present. A systematic review of 35 empirical articles reveals that most studies employed a quantitative approach, particularly quasi-experimental methods, to assess STEAM’s impact on student learning outcomes. Project-based learning (PjBL) and problem-based learning (PBL) were the dominant instructional models, significantly enhancing critical thinking, problem-solving, communication, and collaboration skills. Some studies integrated local wisdom and technology-based tools such as e-modules, augmented reality (AR), and e-comics to boost engagement. However, limited qualitative research explores students' and teachers' experiences, and few long-term studies assess STEAM’s sustained impact. Research remains concentrated on primary and secondary education, with minimal focus on higher or vocational education, crucial for workforce readiness. Additionally, while critical thinking skills have improved, fostering creativity remains a challenge. Future research should incorporate qualitative and mixed-methods approaches, conduct longitudinal studies, and develop reliable STEAM assessment instruments to enhance implementation across diverse educational contexts.